Barriers to physical activity among high school students in the Maule Region - Merellano-Navarro, Eugenio; Binimelis-Fuentes, Julissa; Estay-Bravo, Fabian; Gallegos-Pizarro, Daniela; Guerrero-Conejera, José; Etchevers-Rivas, Valentina (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Despite the growing scientific interest in physical inactivity, it is still not possible to improve the indicators; therefore, it is necessary to identify the barriers that prevent schoolchildren from maintaining healthy habits. This study aimed to identify the barriers to physical activity among secondary school students in the central-southern area of Chile. This was a quantitative, descriptive-correlational, cross-sectional study. The sample was one of convenience and consisted of 753 secondary school students—285 females (37.9%) and 459 males (61%)—from public and private schools in central-southern Chile. A battery of questionnaires was applied, compiling various validated instruments for this population, considering the following areas: a) socio-demographic data; b) physical activity; c) barriers to physical activity. A total of 96.9% of the sample did not comply with WHO recommendations and reported 334.52 minutes of sedentary behaviors. Regarding perceived barriers to physical activity, women reported higher scores on barriers than men. Total meets possessed a significant correlation with all barriers analyzed, while age was only correlated with the barrier of task incompatibility (r=0.148, p<0.05). Although adolescents report high or moderate levels of physical activity, they do not meet the recommended physical activity. In addition, task incompatibility is the highest barrier perceived by adolescents in both genders, while, in females, self-concept is added as one with the highest values.